Gender differences of health literacy in first and second generation migrants: A systematic review. (13th November 2019) - Chakraverty, D; Baumeister, A; Aldin, A; Monsef, I; Jakob, T; Seven, ÜS; Anapa, G; Skoetz, N; Woopen, C; Kalbe, E
Abstract: Background: Health literacy, defined as all skills and capabilities that enable a person to access, understand, appraise and apply health information, is a key factor regarding disease management, health outcomes, and health-decision-making. Internationally, migrants have been identified as a high-risk group for limited health literacy. However, it remains unclear if female and male migrants process health information differently. This systematic review aims to analyze gender differences in the health literacy of first and second generation migrants. Methods: We performed a systematic review according to PRISMA guidelines. We searched OVID (MEDLINE), PsychInfo and CINAHL for original articles providing extractable data on the health literacy of male and/or female migrants. Two reviewers independently reviewed abstracts and full text articles for according to predefined inclusion criteria, including the use of a validated health literacy measurement tool, applying it to first and/or second generation adult migrants. We adapted a data extraction sheet from the Cochrane Collaboration for extracting relevant data. The included studies were evaluated against a standardized set of quality criteria. Results: Our search yielded 3411 records. We included 48 studies, of which 37 were conducted in the USA and Canada, with 22 focusing Hispanic and Asian immigrants' functional health literacy; the nine European studies examined a variety of work migrants and refugees using a comprehensive approach (e.g. measured by the HLS-EU-Q47). Thus, a strong heterogeneity in defining and measuring health literacy and in the populations examined can be stated. 15 studies exclusively examined the health literacy of women; none dealt with men only. Conclusions: The heterogeneity in defining and measuring health literacy in migrants as well as the diversity of the populations studied make it difficult to compare international research in this area. There is a lack of research focusing male migrants. Key messages: International research on health literacy with gender-specific data on migrants reveals a strong heterogeneity in defining and measuring health literacy. International research on health literacy with gender-specific data on migrants reveals a lack of studies regarding male migrants' health literacy.